2011
DOI: 10.1111/j.2042-7174.2011.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the views and attitudes of Scottish pharmacists to continuing professional development

Abstract: Using principal component analysis has identified four factors associated with Scottish pharmacists' views and attitudes to CPD. This may provide an approach to facilitate comparison of CPD views and attitudes with intra and inter professional groupings. Further study may allow identification of good practice and solutions to common CPD issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 11 publications
3
36
1
Order By: Relevance
“…ADAPT participation findings regarding constraints and supports are consistent with other studies illustrating associations with positive and negative attitudes of pharmacists toward continuing professional development in general [29]. Studies of online faculty development programmes have similarly identified factors affecting participation including perceived need or usefulness of the content, technical challenges and assistance, clear expectations and time to complete activities; however, definitions of participation and mechanisms for measurement varied [30].…”
Section: Discussionsupporting
confidence: 82%
“…ADAPT participation findings regarding constraints and supports are consistent with other studies illustrating associations with positive and negative attitudes of pharmacists toward continuing professional development in general [29]. Studies of online faculty development programmes have similarly identified factors affecting participation including perceived need or usefulness of the content, technical challenges and assistance, clear expectations and time to complete activities; however, definitions of participation and mechanisms for measurement varied [30].…”
Section: Discussionsupporting
confidence: 82%
“…Follow up data on reasons for the low interest levels was not available, however, this may not be unrelated to evidence from studies in other countries that indicate that lack of knowledge about MCPD, poor access to the internet, time constraints and high monetary cost contribute to low uptake [46, 47]. Our finding is similar to that from studies in Scotland and USA that also show that there is a general lack of motivation and low level of knowledge of pharmacists on the benefits of continuing development programmes [48, 49]. Increased sensitization and timely provision of MCPD related information may increase uptake in Nigeria.…”
Section: Discussionsupporting
confidence: 80%
“…Having confidence in the format and process of learning will increase participation, as well as having support in the workplace. Power et al (2011) [48] noted that hospital pharmacists are more confident in the process than community pharmacists. It is also important to recognize that a range of learning formats should be used and topics need to be targeted to those individuals motivated to learn [49].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research by Schindel et al (2012) shows that pharmacists value face-to-face training [49]. With a variety of face-to-face methods available, it is vital to give participants choice, ensuring information is presented in a way that is tailored to their learning style [48].…”
Section: Discussionmentioning
confidence: 99%